Panel and Appellate Body Interpretation on the Most-Favoured Nation Treatment Obligation under the General Agreement on Trade in Services - Krisna Arjati, Dwi; Dalem Dahana, Cokorda (Kertha Negara : Journal Ilmu Hukum; Vol. 05, No. 02, April 2017, 2017)
This article discusses various interpretations of the provisions that govern the Most-Favoured Nation Treatment (MFN) obligation in accordance with the General Agreement on Trade in Services (GATS) within the framework of the World Trade Organization (WTO). It is a normative legal research that uses instrumental (statutory) and case approaches. This writing concludes that the Panels and Appellate Bodies of the WTO have provided a number of interpretations of the provisions of GATS related to MFN treatment obligations, which later became jurisprudence.
Keywords: Interpretation, Most-Favoured Nation, World Trade Organization